2019
DOI: 10.1126/sciadv.aaw5685
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic magnetic topological insulators in van der Waals layered MnBi 2 Te 4 -family materials

Abstract: The interplay of magnetism and topology is a key research subject in condensed matter physics, which offers great opportunities to explore emerging new physics, such as the quantum anomalous Hall (QAH) effect, axion electrodynamics, and Majorana fermions. However, these exotic physical effects have rarely been realized experimentally because of the lack of suitable working materials. Here, we predict a series of van der Waals layered MnBi2Te4-related materials that show intralayer ferromagnetic and interlayer … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

35
726
3
19

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 889 publications
(783 citation statements)
references
References 68 publications
35
726
3
19
Order By: Relevance
“…As a consequence, the ground state of EuCd 2 As 2 becomes a novel axion insulator state which is not studied in previous theoretical paper 14. This ground state is similar to that reported recently in the MnBi 2 Te 4 family 17,18. But for EuCd 2 As 2 , massless Dirac surface states appear on some specifically oriented surfaces which are protected by the mirror or TL symmetries.…”
Section: The Number Of Occupied Bands With Even and Odd Parity At Thesupporting
confidence: 79%
See 1 more Smart Citation
“…As a consequence, the ground state of EuCd 2 As 2 becomes a novel axion insulator state which is not studied in previous theoretical paper 14. This ground state is similar to that reported recently in the MnBi 2 Te 4 family 17,18. But for EuCd 2 As 2 , massless Dirac surface states appear on some specifically oriented surfaces which are protected by the mirror or TL symmetries.…”
Section: The Number Of Occupied Bands With Even and Odd Parity At Thesupporting
confidence: 79%
“…Furthermore, it was shown that for other surfaces, there are gaped surface states contributing to half‐quantized anomalous Hall conductivity. This class of AFM materials was coined as AFM TIs, and as a possible candidate for an axion insulator, as reported recently for MnBi 2 Te 4 17–21. However, the topological nature of the surface of MnBi 2 Te 4 remains puzzling due to disagreements between experimental results and theoretical predictions 19–21.…”
Section: The Number Of Occupied Bands With Even and Odd Parity At Thementioning
confidence: 95%
“…Generally, after sample cleavage, the new surface of bulk MnBi 2 Te 4 is divided into two parts (layers) according to the depth from the topmost layer (see schematic in Fig. 4D): (i) the top layer with the thickness of few nanometers, which hosts an embedded Dirac cone structure due to the unclear magnetic order (26,27,38); (ii) the deep layer with the predicted out-of-plane antiferromagnetic order (18,19). Depending on the detection depths of different techniques, the top layer is detectable to surface sensitive techniques, such as STM and ARPES, while the deep intrinsic layer is detectable to bulk sensitive techniques such as transport measurements.…”
Section: Figurementioning
confidence: 99%
“…For example, the observations of magnetism-induced gap opening at the Dirac point are either too large or too small (absent) (17)(18)(19)(23)(24)(25)(26)(27)(28) and the assignment of the topological surface states are still controversial (26)(27)(28). Here we employ scanning tunneling microscopy (STM) to systematically study the electronic structure of MnBi 2 Te 4 in both real and momentum spaces, and the complementary information helps us to have a better understanding of the material.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond MnBi 2 Te 4 , other vdW superlattice-like Mn-Bi-Te structures with tunable chemical formulas as (MnBi 2 Te 4 ) m (Bi 2 Te 3 ) n (where m and n are integer) have also been proposed [18,[24][25][26]. Through tuning numbers of layers, stacking configurations, or compositions, these vdW heterostructures have been further proposed to investigate rich topological quantum phenomena between magnetism and topology, such as QAH phases [18,20,23], axion insulator states [22], antiferromagnetic TIs [21,22], and their phase transitions [18]. These advances mentioned above forward a strategy for investigating magnetic topological phases and especially QAH effects in vdW layered materials.…”
mentioning
confidence: 99%